2007
DOI: 10.1590/s0100-736x2007001000007
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection by porcine circovirus type 2 and porcine parvovirus in aborted fetuses and stillborn piglets in southern Brazil

Abstract: Porcine circovirus types 1 and 2 (PCV1, PCV2) and porcine parvovirus (PPV) are widespread in pig populations around the world. Nevertheless, only PCV2 has been associated with different clinical syndromes, thus representing a major problem to the pig industry. The association of cases of swine abortions and stillborns with PCV1 and PCV2 and PPV was studied retrospectively (2005-2007). Additional pathogens were also investigated in lesioned fetuses. The studied litters included stillborn piglets and several mum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
1
16
1
9
Order By: Relevance
“…Pescador (2007) confirmed that E. coli was detected as co-infection with PCV2 in cases positive for mesocolic edema.…”
Section: Discussionsupporting
confidence: 66%
“…Pescador (2007) confirmed that E. coli was detected as co-infection with PCV2 in cases positive for mesocolic edema.…”
Section: Discussionsupporting
confidence: 66%
“…Studies have revealed that Brazilian pig herds are commonly infected with economically important viruses, including porcine rotavirus groups A, B and C; hepatitis E virus; Aichivirus C; porcine norovirus; porcine enteric picornaviruses; porcine parvovirus; porcine circovirus type 2 and torque teno sus virus, some of which lead to public health concerns (Pescador et al 2007;Barry et al 2008b;Zlotowski et al 2008;Cunha et al 2010;Lorenzetti et al 2011;Médici et al 2011;Gardinali et al 2012;Ritterbusch et al 2012;de Arruda Leme et al 2013Ribeiro et al 2013;Donin et al 2014;Silva et al 2014;Stipp et al 2014). It is not unusual to find pigs infected with several of these viruses at the same time (Pescador et al 2007;Zlotowski et al 2008;Médici et al 2011;Lorenzetti et al 2011;Donin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also observed that the OR increased to 22.7 (P<0.0001) when there was co-infection with both viruses. Other studies reported association between PCV2 and PPV and the development of diseases such as post weaning multisystemic wasting syndrome in pigs (PMWS), renal lesions, and reproductive failures (Allan et al 1999, Kim & Chae 2004, Fernandes et al 2006, Pescador et al 2007). …”
Section: Discussionmentioning
confidence: 99%